PENGARUH LOCUS OF CONTROL, ORGANIZATION COMMITMENT, PERFORMANCE, DAN TURNOVER INTENTION TERHADAP DYSFUNCTIONAL AUDIT BEHAVIOR PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN DI SUMATERA UTARA - Sitorus, Jessy Safitri; Siburian, Welni Kiki; Siagian, Feby Fitriani; Gultom, Yohana (EDUTECH CONSULTANT, 2019)
The aim of this study was determined the effect of the auditor's personal characteristics on Dysfunctional audit behavior specifically to determine the Effect of Locus of Control, Organization commitment, Performance, and Turnover Intention on Dysfunctional Audit Behavior. It used primary data in the form of questionnaires. The subjects of this study were 120 auditors that working at the Financial and Development Supervisory Board in North Sumatras. Sampling technique was use Convinience Sampling. To analized the data results, researchers used the SPSS version 19.0 with significant level of 5%. The results of this study indicated that simultaneous locus of control, organizational commitment, performance, and turnover intention had a significant effect on behavioral audit behavior, whereas there was no significant effect on Locus of control, performance, and turnover intention on the Dysfunctional Audit Behavior. The Organization Commitment partially had a significant effect on dysfunctional audit behavior.